Comparative analysis of cost and time for beam, slab, and column formwork using conventional and aluminum formwork methods - Matildah Pretty Putri Alkassa; Sudarno P Tampubolon; Agnes Sri Mulyani (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
The development of the construction industry in Indonesia has accelerated urbanization and population growth, demanding the implementation of efficient construction methods, particularly in the development of high-rise buildings that optimize both cost and project duration. In reinforced concrete construction, formwork plays a significant role in determining the overall cost and time of the construction project. Therefore, this study analysis the comparison of cost and time for formwork work on columns, beams, and slabs in the BSI Tower project. Conventional formwork, typically made of wood, is still widely used due to its relatively low initial cost and flexibility. However, this method has several drawbacks, including material waste, low durability, high labour intensity, long processing time, inconsistent concrete surface quality, and a short service life, which lead to higher maintenance and replacement costs. In contrast, aluminum formwork is lightweight, precise, and reusable. This research employs a quantitative approach and utilizes Microsoft Project software. Cost analysis is conducted by multiplying the work volume by unit prices obtained from the 2024 Jakarta Standard Unit Price Analysis (AHSP) and project documentation, while time analysis is developed through Microsoft Project to estimate the duration of formwork installation and removal from floors 14 to 22. The results indicate that aluminum formwork is more efficient than conventional formwork in terms of both cost and time. The total cost of the aluminum formwork system was IDR 6,262,395,602, while the total cost of the conventional formwork system was IDR 6,509,110,236. This indicates that the aluminum formwork system is more economical, with a cost reduction of IDR 246,714,634, equivalent to approximately 3.79% compared to the conventional formwork system. Regarding time, aluminum formwork requires 63 days to complete, whereas conventional formwork takes 108 days, resulting in a time saving of 45 days. This research provides a data-driven framework to assist contractors in optimizing project scheduling and cost budgeting when transitioning from conventional formwork to aluminum formwork systems.